Early onset of efficacy with erenumab for migraine prevention in Japanese patients: Analysis of two randomized, double‐blind, placebo‐controlled studies. Issue 3 (24th February 2022) - Hirata, Koichi; Takeshima, Takao; Sakai, Fumihiko; Imai, Noboru; Matsumori, Yasuhiko; Tatsuoka, Yoshihisa; Numachi, Yotaro; Yoshida, Ryuji; Peng, Cheng; Mikol, Daniel D.; Lima, Gabriel Paiva da Silva; Cheng, Sunfa
Abstract: Purpose: In two 24‐week migraine prevention studies in Japan, erenumab was associated with significantly greater reductions in migraine frequency versus placebo over Weeks 13–24 (primary endpoint). This post hoc analysis evaluated the onset of efficacy within the first 4 weeks after the initiation of erenumab from the 24‐week double‐blind periods of these studies. Methods: Placebo‐adjusted differences in least squares mean (LSM) change from baseline in weekly migraine days (WMD) were assessed weekly in each study and by migraine type (episodic (EM]/chronic [CM]) (Study 20170609). Results: A total of 407 patients from Study 20120309 (70 mg: N = 135; 140 mg: N = 136; placebo: N = 136) and 261 patients from Study 20170609 ([EM] 70 mg: N = 78; placebo: N = 81; [CM] 70 mg: N = 52; placebo: N = 50) were included. For Study 20120309, onset of efficacy was observed as early as Week 1 in favor of erenumab versus placebo. Placebo‐adjusted differences in LSM (95% confidence interval [CI]) change from baseline in WMD at Week 1 were −0.38 (−0.71 to −0.05; p  = .022) and −0.49 (−0.82 to −0.16; p  = .004) in favor of erenumab 70 and 140 mg, respectively. For Study 20170609, significant placebo‐adjusted differences were observed with erenumab 70 mg at Week 1 in patients with EM (LSM [95% CI]: −0.55 [−0.97 to −0.12; p  = .012]), and at Week 2 in patients with CM (LSM [95% CI]: −0.81 [−1.53 to −0.09; p  = .028]) and for the overall population (LSM [95% CI]: −0.71 [−1.09 to −0.33; p  < .001]). Conclusions: Erenumab treatment significantly reduced WMD compared with placebo. Onset of erenumab efficacy occurred as early as Week 1 in patients with migraine.